THE IMPLEMENTATION OF CRIMINAL LAW IN SOCIAL FUNDS CORRUPTION - Duahido, Dhamura; Kunarso, Kunarso (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2022)
Corruption is highly detrimental to state finances and obstructs national development. It must be completely eradicated to create an impartial and prosperous society based on Pancasila and the 1945 Constitution. Corruption not only causes financial losses to the country but also hinders the growth and sustainability of national development, which demands high efficiency. The corruption court's consideration of defendants who misused humanitarian aid funds plays a crucial role in determining mitigating decisions. This raises the question of what the judge’s decision should be in imposing the toughest sanctions for corruption defendants involved in the misuse of humanitarian aid funds. This research is normative legal research that focuses on positive legal norms, particularly regarding maximum and minimum regulations. Mitigating factors presented during the trial process become key considerations for the panel of judges in making their decision. In imposing sentences, the panel of judges has implemented a double-track system.